Clostridium perfringens in central Colombia (2024)
Clostridium perfringens is an opportunistic bacterium that causes intestinal diseases in both humans and animals. This study aimed to assess the frequency of C. perfringens and the presence of toxin-encoding genes in fecal samples from individuals with or without gastrointestinal symptoms in the Department of Boyacá, Colombia. Additionally, risk factors associated with carriage and disease development were analyzed. A total of 114 stool samples were analyzed using a molecular test based on specific polymerase chain reaction (PCR) targeting 16S-rRNA and alpha toxin (cpa) genes. For individuals with a positive result for the PCR test, stool samples were cultured on Tryptose Sulfite Cycloserine (TSC) agar. Two to five colonies forming units were selected based on phenotypic characteristics, resulting in 56 bacterial isolates. These isolates were then analyzed for toxin-coding genes associated with gastrointestinal diseases. In addition, sociodemographic and clinical data from 77 individuals were also analyzed. The overall frequency of C. perfringens was 19.3% (n = 22/114). The detection frequency in 77 individuals with clinical data was 16.6% (n = 5/30) among symptomatic individuals and 21.2% (n = 10/47) among asymptomatic individuals. All 56 isolates obtained carried the cpa gene, while cpb2 was present in 10.7% (n = 6/56)